Health and disability insurance - Axel Börsch-Supan (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
Disability insurance - the insurance against the loss of the ability to work - is a substantial part of social security expenditures in many countries. The benefit recipiency rates in disability insurance vary strikingly across European countries and the US. This paper investigates the extent of, and the causes for, this variation, using econometric analyses based on new data from SHARE, ELSA and HRS. We show that even after controlling for differences in the demographic structure and health status these differences remain. This holds for a broad set of objective and subjective physical and mental health measures as well as for contemporal, intertemporal and life-course specifications of health, including measures of childhood health. In turn, indicators of disability insurance generosity explain 75% of the cross-national variation. We conclude that it is not health but the country-specific design of early retirement and labor market institutions, and especially disability insurance rules, which explain the observed cross-country variation in the receipt of disability benefits.
Keywords: D31; D63; I30; J11; 330; Erwerbsminderungsrente - internationaler Vergleich; Sozialausgaben; Erwerbsminderung; psychische Faktoren; medizinische Faktoren; Gesundheitszustand; institutionelle Faktoren; Leistungsanspruch; Anspruchsvoraussetzung; Rentenbezug; Dänemark; Schweden; Österreich; Bundesrepublik Deutschland; Frankreich; Belgien; Niederlande; Schweiz; Griechenland; Italien; Spanien; Tschechische Republik; Irland; Israel; Polen; Großbritannien; USA